Mutational screening of inverted formin 2 in adult-onset focal segmental glomerulosclerosis or minimal change patients from the Czech Republic - Safarikova, Marketa; Stekrova, Jitka; Honsova, Eva; Horinova, Vera; Tesar, Vladimir; Reiterova, Jana (BMC medical genetics, 2018)
BACKGROUND: Mutations in INF2 are frequently responsible for focal segmental glomerulosclerosis (FSGS), which is a common cause of end stage renal disease (ESRD); additionally, they are also connected with Charcot-Marie-Tooth neuropathy. INF2 encodes for inverted formin 2. This protein participates in regulation of the dynamics of the actin cytoskeleton, involving not only the polymerisation, but also the depolymerisation of filaments. The present study is the first mutational analysis of INF2 done in the Czech Republic. METHODS: Mutational analysis of INF2 was performed on 109 patients (mean age at onset 41.44 ± 18.91 years) with FSGS or minimal change disease (MCD); and also in 6 patients without renal biopsy who had already developed chronic kidney disease (CKD)/ESRD at the time of diagnosis. We used high resolution melting method (HRM), with subsequent Sanger sequencing, in suspect samples from HRM analysis. The HRM method is an effective method for the screening of large cohorts of patients. RESULTS: Two pathogenic mutations (p.Arg214His and p.Arg218Gln) were detected in INF2. The first (p.Arg214His) was identified in the FSGS patient with a positive family history. The second mutation (p.Arg218Gln) was found in two brothers with ESRD of unknown etiology. The most frequent sequence change was the substitution p.P35P, the incidence of which corresponded with the frequencies available in the ExAC Browser and gnomAD Browser databases. This analysis also detected different exonic and intronic changes that probably did not influence the phenotype of the included patients. CONCLUSIONS: The INF2 mutational screening is useful in familial FSGS cases as well as in patients with an unknown cause for their ESRD, but with a positive family history. INF2 seems to be not only the cause of FSGS, but also of ESRD of unknown etiology. Our study has confirmed that the HRM analysis is a very useful method for the identification of single nucleotide substitutions.
Keywords: mutace; dospělí; High resolution melting method; Female; Phenotype; chronické selhání ledvin; INF2; Adult; Glomerulosclerosis, Focal Segmental; ženské pohlaví; mutační analýza DNA; introny; Minimal change disease; mikrofilamentové proteiny; lidé; Introns; DNA Mutational Analysis; Mutation; Focal segmental glomerulosclerosis; Kidney Failure, Chronic; Charcotova-Marieova-Toothova nemoc; kohortové studie; End stage renal disease; Cohort Studies; Male; forminy; Czech Republic; Exons; Česká republika; exony; fenotyp; mužské pohlaví; Charcot-Marie-Tooth Disease; fokálně segmentální glomeruloskleróza; Microfilament Proteins; Formins; Humans